Bahan Ajar Cerita Rakyat sebagai Perancah Pendidikan Karakter (Folklore Teaching Materials as a Character Education Scaffold) - Suherli Kusmana; Bela Nurzaman (Indonesian Language Education and Literature, 2021)
This study aims to obtain folklore teaching materials as a character education scaffold. The folklore studied was taken from the environment of Cirebon community students. The research method used is research and development. The stages carried out are (1) initial collection and analysis of folklore, textbooks used, and the need for teaching materials; (2) development of teaching materials design and validation; (3) reconstruction of teaching materials based on input from expert validation results; (4) evaluation through the feasibility test for use in learning in schools; and (5) implementation of teaching materials in learning. The results showed that the development of affective competence through folklore is a scaffold for students' character education. The development of character education is used to develop ideas or ideas in compiling short stories. Character education is carried out through teaching materials containing the values of local wisdom of folklore into short stories.Penelitian ini bertujuan untuk mendapatkan bahan ajar cerita rakyat sebagai perancah pendidikan karakter. Cerita rakyat yang diteliti diambil dari lingkungan peserta didik masyarakat Cirebon. Metode penelitian yang digunakan adalah penelitian dan pengembangan. Adapun tahapan yang dilakukan adalah: (1) pengumpulan dan analisis awal cerita rakyat, buku teks yang digunakan, dan kebutuhan bahan ajar; (2) pengembangan desain bahan ajar dan validasi; (3) rekonstruksi ulang bahan ajar berdasarkan masukan hasil validasi ahli; (4) evaluasi melalui uji kelayakan penggunaan dalam pembelajaran di sekolah; dan (5) implementasi bahan ajar dalam pembelajaran. Hasil penelitian menunjukkan bahwa pengembangan kompetensi afektif melalui cerita rakyat merupakan perancah (scaffolding) bagi pendidikan karakter siswa. Pengembangan pendidikan karakter dimanfaatkan untuk mengembangkan ide atau gagasan dalam menyusun cerita pendek. Pendidikan karakter dilakukan melalui bahan ajar bermuatan nilai-nilai kearifan lokal cerita rakyat ke dalam cerita pendek.